Covid-19 pandemic and global health workers’ mortality: Challenges, implications and prognosis of action for Nigeria Health care delivery system (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
COVID-19 is one of the pandemics in the world with the widest spread in terms of shortness of time and space coverage. Very few countries in the world are spared so far. Incidence of death is very high occasioned by COVID-19, especially among health care workers fighting the pandemic which constitutes 10% of global mortality due to COVID-19. Ex-post facto exploratory analysis was used covering December 2019 to end of April, 2020 relying on secondary data professionally sourced in line with the independent variable COVID-19 pandemic and the dependent variable health workers’ mortality. COVID-19 history, symptoms, transmission, containing strategies, were examined in view of attendant mortality, especially of health workers. Analysis was made following functional theory. It was concluded that COVID-19 caused high mortality which endangered health workers of all categories, especially skilled health workers like doctors and nurses. Increasing health workers mortality will cause lack of professionals to manage health facilities in developing countries like Nigeria and impede on the possibility of attaining skilled health workers density, which is a strategic component of achieving Sustainable Development Goals. It was recommended among others that personal protection and test kits should be provided by government, international agencies and humanitarian concerns, and health workers should be given adequate training on management of COVID-19.
Keywords: COVID-19; Pandemic; Health workers; Mortality; Healthcare delivery system; Sustainable development goals; Health workers density